(untitled) - Yasir Ashraf ,S. Sampath Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study was set out to investigate the cultural constraints that hinder girls’ education in Bandipora District in Kashmir Division; India Three hypotheses were formulated to guide the study. The design of the research adopted in this research is cross sectional in nature. The researcher made use of systematic random sampling technique to select 404 girls from Government Degree Colleges of Bandipora District of Kashmir Division. The researcher made use of a self-developed instrument with 07 items both positive as well negative. The instrument has a Cronbach alpha reliability coefficient of 0.646. The instrument had facial and content validity. It also had language appropriateness. The researcher administered 450 copies of the questionnaire on the respondents and 404 copies of the questionnaire were retrieved back. The data generated from the field was collated and the mean score analysis for the 07 items was carried out in order to provide answer to the research hypotheses and a scoring procedure with a mean score of 0.00-2.50 for lower levels and the second one assess the higher levels with a mean score of 2.51- 5.00. The Chi-Square test was used to test the hypotheses at a significant level of 0.05. The investigation denotes that more than fifty percent of the girls are in the age group of up to 20 years and little less than eighty percent of them are living in rural areas and more than half of the girls have joint family background. Also it is revealed that more than thirty five percent of the girls agreed that their family members were optimistic towards their higher education. Being visible in public sphere during to and fro to college is not encouraged in culture was disagreed by nearly thirty five percent of the girls. However nearly thirty percent of the girls agree with the statement that they have the lack of permission to study in other far off places. Moreover it is observed that irrespective of the age, girls have encountered lower cultural constraints in accessing higher education with varied intensity.